2006
DOI: 10.1152/ajpheart.00566.2006
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training blunts microvascular rarefaction in the metabolic syndrome

Abstract: son, and Randall Bryner. Exercise training blunts microvascular rarefaction in the metabolic syndrome. Am J Physiol Heart Circ Physiol 291: H2483-H2492, 2006. First published June 23, 2006 doi:10.1152/ajpheart.00566.2006.-Reduced skeletal muscle microvessel density (MVD) in the obese Zucker rat (OZR) model of the metabolic syndrome is a function of a chronic reduction in vascular nitric oxide (NO) bioavailability. Previous studies suggest that exercise can improve NO bioavailability and reduce chronic inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
75
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 51 publications
(76 reference statements)
6
75
0
1
Order By: Relevance
“…Boor et al do not mention if the rats were fasted overnight, and the triglyceride levels in their study might reflect postprandial/random levels. In addition, our results are similar to those of Frisbee et al (24) who, using 10 wk of exercise and an overnight fasting period, observed a similar decrease in triglyceride levels.…”
Section: Discussionsupporting
confidence: 93%
“…Boor et al do not mention if the rats were fasted overnight, and the triglyceride levels in their study might reflect postprandial/random levels. In addition, our results are similar to those of Frisbee et al (24) who, using 10 wk of exercise and an overnight fasting period, observed a similar decrease in triglyceride levels.…”
Section: Discussionsupporting
confidence: 93%
“…Although the OZR is significantly less active than the LZR (9), OZRs have much greater body mass, and this should provide a greater stimulus for muscle growth on the weight-bearing muscles. Nevertheless, a previous study from our laboratory in which the daily activity of the OZR was increased through daily treadmill running demonstrated no increase in the size of their skeletal muscles (18). These findings suggest that there may be an underlying deficit in the ability of skeletal muscle to respond to increased loading in the OZR model of metabolic syndrome.…”
mentioning
confidence: 51%
“…There is an additional lower rate of microvessel loss after 17 wk of age, but our unpublished work suggests that net microvessel loss develops asymptotic behavior after 17 wk of age. What was most interesting about this observation is that our previous results suggested that the change in skeletal muscle microvessel density would parallel the changes to vascular NO bioavailability (21,23). However, as demonstrated in Figs.…”
Section: Discussionmentioning
confidence: 63%
“…As defined by Goligorsky (26), microvascular rarefaction is a form of microvascular adaptation in response to a challenged or disease state that results in a reduction in arteriolar or capillary density within an affected tissue. In OZR, this process plateaus at an ϳ25% reduction in microvessel density compared with control levels in LZR (21,42,48), with clear implications for mass transport/ exchange and muscle fatigue resistance (46). Furthermore, previous results have demonstrated that this response is not dependent on the development of hypertension in OZR (22) and that it is associated with the development of insulin resistance and low bioavailability of nitric oxide (NO) within the microvasculature (23).…”
mentioning
confidence: 99%